Vice-Chancellor's Awards 2023 - Student Experience - Andreou, Christoforos K. (My University, 2026)
I won the Vice-Chancellor's Award 2023 in the Student Experience category at the University of Southampton, becoming the first academic from the Department of Banking and Finance of Southampton Business School to win a Vice-Chancellor's Award since the department's inception.
Keywords: Social sciences